(untitled) - Roth, Charles H. (Toronto, 2008)
This texbook is intened for a senior-level course in digital systems design. The book covers both basic principles of digital system design and the use of a hardware description language, VJDL in the design process. After basic principles have been covered, design is best taught by using examples.
Keywords: VHDL (Computer hardware description language),System design,Electronic digital computers,Hệ thống thiết kế,VHDL (Ngôn ngữ lập trình); Data processing,Circuits,Computer-aided design,Xử lý dữ liệu